PENGARUH MEDIA PEMBELAJARAN BERBASIS MOODLE TERHADAP PENINGKATAN KEMAMPUAN GENERIK SAINS SISWA SMK - Desak Made Anggraeni; Susilawati Susilawati; Gunawan Gunawan (Jurnal Penelitian Pendidikan IPA, 2015)
The purpose of this study was to determine the influence of media-based learning moodle to increase students' generic skills in materials science impulse and momentum. The method used is the method of quasi-experimental research design with untreated control group design with pretest and posttest. A total of 53 students were divided into experimental group and control group were included in this study. Research instruments using generic science skills test in the form of descriptions about. Data analysis using the test "mean-difference" and "normalized gain scores". Based on the results of this study concluded that the use of media-based learning moodle does not result in a significant increase in the ability of generic science class experiment between students and classroom control. But based on the achievement of values, the average value of the ability of generic science experiments grade higher than the control class. Keywords: Moodle-Based Learning Media, Generic Skills